Inadequate Gonadal Replacement in Patients with Turner Syndrome may Result in Pituitary Volume Enlargement - Akkus, Gamze; Kolsuz, İrem and Sözütok, Sinan and Onan, Bilen and Karagun, Barış and Evran, Mehtap and Sert, Murat and Tetiker, Tamer (Current Medical Imaging, 2025)
ObjectivesPatients with Turner syndrome need hormone replacement therapy for puberty induction. However, it is not known whether inadequate hormone replacement therapy affects the pituitary.Material and MethodsPatients with Turner syndrome (n=35) and healthy control (n=20) (age/gender matched) subjects were included. MRI imaging of the pituitary was used to calculate pituitary volumes. According to the estradiol regimen, patients were divided into two groups; (i) those treated with low-dose conjugated oestrogen (CE, 0.625 mg) and (ii) those treated with combination therapy (ethinyl estradiol+sipropterone acetate; 35 mcg/2 mg). Pituitary measurements were calculated according to pituitary borders and their distances to each other via pituitary MRI.ResultsPituitary hyperplasia (0.58±0.15 cm3vs. 0.40±0.17 cm3) was determined in patients with low dose conjugated estrogen compared to the other patients or healthy control subjects (0.42±0.16 cm3) (p=0.005). Serum FSH levels of the patients treated with low dose CE were also higher compared to the patients who received combination therapy (p=0.001).ConclusionInadequate hormone replacement therapy can cause devastating effects on the bones and uterine health and disrupts the pituitary structure.
Keywords: Hormone replacement therapy